Microenvironmental cues for T‐cell acute lymphoblastic leukemia development. Issue 1 (May 2016) - Passaro, Diana; Quang, Christine Tran; Ghysdael, Jacques
Summary: Intensive chemotherapy regimens have led to a substantial improvement in the cure rate of patients suffering from T‐cell acute lymphoblastic leukemia (T‐ALL). Despite this progress, about 15% and 50% of pediatric and adult cases, respectively, show resistance to treatment or relapse with dismal prognosis, calling for further therapeutic investigations. T‐ALL is an heterogeneous disease, which presents intrinsic alterations leading to aberrant expression of transcription factors normally involved in hematopoietic stem/progenitor cell development and mutations in genes implicated in the regulation of cell cycle progression, apoptosis, and T‐cell development. Gene expression profiling allowed the classification of T‐ALL into defined molecular subgroups that mostly reflects the stage of their differentiation arrest. So far this knowledge has not translated into novel, targeted therapy. Recent evidence points to the importance of extrinsic signaling cues in controlling the ability of T‐ALL to home, survive, and proliferate, thus offering the perspective of new therapeutic options. This review summarizes the present understanding of the interactions between hematopoietic cells and bone marrow/thymic niches during normal hematopoiesis, describes the main signaling pathways implicated in this dialog, and finally highlights how malignant T cells rely on specific niches to maintain their ability to sustain and propagate leukemia.